The potential benefit of leptin therapy against amyotrophic lateral sclerosis (ALS). Issue 1 (21st December 2021) - Ferrer‐Donato, Agueda; Contreras, Ana; Fernandez, Paloma; Fernandez‐Martos, Carmen M.
Abstract: Background: Targeting leptin could represent a rational strategy to treat amyotrophic lateral sclerosis (ALS), as previously clinical studies have shown its levels to be associated with a lower risk of ALS disease. However, very little is known about the potential influence of leptin in altering disease progression in ALS, as it has thus far been correlated with the protection exerted by increased fat mass stores. Methods: We studied the impact of leptin treatment beginning at 42‐days of age (asymptomatic stage of disease) in the TDP‐43 (TDP43 A315T ) transgenic (Tg) ALS mouse model. Results: Our study shows that leptin treatment was associated with altered expression of adipokines and metabolic proteins in TDP43 A315T mice. We also observed that weight loss decline was less prominent after leptin treatment in TDP43 A315T mice relative to vehicle‐treated animals. In TDP43 A315T mice treated with leptin the disease duration lasted longer along with an improvement in motor performance relative to vehicle‐treated animals. Conclusions: Collectively, our results support leptin as a potential novel treatment approach for ALS. Abstract : There is an urgent need to improve upon current approaches to amyotrophic lateral sclerosis (ALS). In this study, we evaluated in vivo the impact of leptin treatment in a very well validated mouse model of TDP‐43 proteinopathy (TDP‐43A315T mice). Collectively, our results support leptin as a potential novel treatment approach for ALS.